Working from home facilitates stock ownership - Lorenz Meister; Lukas Menkhoff (DIW Weekly Report, 2023)
In 2020, there were simultaneous increases in the number of private persons participating on the stock market as well as in the number of employees working from home. Indeed, working from home is a robust determinant of stock ownership and partially explains the increase in 2020, with households without children benefiting the most in this manner. Furthermore, the effect of working from home on stock ownership is largest for low-income earners. Thus, working more from home has complex distributional consequences: It tends to expand the stock owner base by, in a broader sense, decreasing the stock market participation cost. While economic policy should not mandate working from home for the sole purpose of increasing stock ownership, it can facilitate stock market participation in other ways, such as by improving financial education.
Keywords: D31; G11; G51; 330; remote work; income inequality; stock market participation